Factors contributing to eviction from permanent supportive housing: Lessons from HUD-VASH. (April 2017) - Montgomery, Ann Elizabeth; Cusack, Meagan; Szymkowiak, Dorota; Fargo, Jamison; O'Toole, Thomas
Highlights: Drug use disorder increased odds of exiting housing due to eviction by 150%. Acute care related to drug use proximal to time of exit increased likelihood of eviction. An increase in primary medical care and supportive services decreased odds of eviction. Abstract: Introduction: Eviction from housing is associated with several negative outcomes, further exacerbated among high-need populations requiring financial and supportive services to maintain housing stability. This study investigated risk and protective factors—both characteristics and precipitating events of tenant eviction—informing permanent supportive housing (PSH) programs' efforts to identify tenants at risk and intervene. Methods: Using administrative data for a cohort of 20, 146 Veterans participating in PSH, this study assessed differences in Veterans who exited the program due to eviction and Veterans who exited because they accomplished their goals. A series of logistic regressions identified patterns of health services use that may signal imminent eviction. Results: Veterans with a drug use disorder and those who received inpatient, emergency, or outpatient care related to mental/behavioral health and substance use conditions proximal to program exit had greater risk for eviction. Receipt of outpatient primary medical care and supportive services was generally protective against eviction. The likelihood of eviction was greatest for Veterans with acute care use within 30 days of exit. Discussion: PSH providers may use these correlates of eviction to identify Veterans in need of an intervention to prevent eviction. Future work should focus on operationalizing these findings and identifying appropriate interventions.